2013
DOI: 10.1148/radiol.12111472
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoprogression of Glioblastoma after Chemo- and Radiation Therapy: Diagnosis by Using Dynamic Susceptibility-weighted Contrast-enhanced Perfusion MR Imaging with Ferumoxytol versus Gadoteridol and Correlation with Survival

Abstract: Purpose:To compare gadoteridol and ferumoxytol for measurement of relative cerebral blood volume (rCBV) in patients with glioblastoma multiforme (GBM) who showed progressive disease at conventional magnetic resonance (MR) imaging after chemo-and radiation therapy (hereafter, chemoradiotherapy) and to correlate rCBV with survival. Materials and Methods:Informed consent was obtained from all participants before enrollment in one of four institutional review board-approved protocols. Contrast agent leakage maps a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
139
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(147 citation statements)
references
References 42 publications
3
139
0
1
Order By: Relevance
“…24,30 Our preliminary findings of USPIO-enhanced imaging in CNSL require further evaluation in studies involving systemic lymphoma. Importantly, USPIO imaging provides a safe alternative for MRI in patients with renal failure.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…24,30 Our preliminary findings of USPIO-enhanced imaging in CNSL require further evaluation in studies involving systemic lymphoma. Importantly, USPIO imaging provides a safe alternative for MRI in patients with renal failure.…”
Section: Resultsmentioning
confidence: 89%
“…USPIO-based DSC perfusion requires neither expensive leakage correlation software algorithms nor preloading with additional doses of USPIO, as is necessary with GBCA. 24 Our limited number of PWIs in CNSL cases in this series do not allow generalization, but will be a subject of future study.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Overall survival was significantly longer in participants with pseudoprogression (35.2 months) compared with those who never experienced pseudoprogression (14.3 months). They concluded that ferumoxytol, used as a blood pool agent, facilitates differentiation between tumor progression and pseudoprogression, appears to be a good prognostic biomarker, and, unlike GBCA, does not require contrast agent leakage correction (139,140) (Figure 18) . Bevacizumab (BEV, Avastin, Genentech, Inc.) is an antivascular endothelial growth factor (VEGF) A antibody working as an angiogenesis inhibitor that normalizes tumor vasculature, and decreases contrast-enhancing tumor volume and blood volume in lesions both in animal models and clinically.…”
Section: Uspio Enhanced Mri For Blood Volume Measurementmentioning
confidence: 99%
“…A pilot study found lesions that enhance on T1WGd and have low rCBV on ferumoxytol-DSC-MRI are more likely to represent pseudoprogression. 52 Gahramanov et al 53 found that ferumoxytol-based measurements of rCBV measurements correlate better with median survival than leak corrected Gd-based measurements. Ferumoxytol also allows the use of steady-state imaging methods, which can produce high-resolution and distortion-free maps of CBV.…”
Section: Contrast Leakmentioning
confidence: 99%